Does the analysis of the enantiomeric composition of clenbuterol in human urine enable the differentiation of illicit clenbuterol administration from food contamination in sports drug testing?. (10th January 2013) - Thevis, Mario; Thomas, Andreas; Beuck, Simon; Butch, Anthony; Dvorak, Jiri; Schänzer, Wilhelm
<x xml:space="preserve">Abstract</x> RATIONALE Clenbuterol (4‐amino‐α‐[(tert‐butylamino)methyl]‐3, 5‐dichlorobenzyl alcohol) is approved for human and veterinary use primarily for the treatment of pulmonary afflictions. Despite the authorized administration in cases of medical indications, the misuse of clenbuterol in animal husbandry as well as elite and amateur sport has frequently been reported, arguably due to growth‐promoting properties. Due to various recent incidences of doping control specimens containing clenbuterol, strategies towards the discrimination of a surreptitious application from unintended intake via animal‐derived edibles or dietary supplements were required. METHODS The enantiomeric compositions of clenbuterol in human urine samples derived from administration studies with therapeutic amounts of the β2‐agonist and authentic doping control specimens were determined. Due to the facts that therapeutic clenbuterol consists of a racemic mixture of (+)‐ and (−)‐stereoisomers and that the first mentioned (dextrorotatory) stereoisomer is retained to a greater extent in edible animal tissue, the differentiation of a recent administration of therapeutic (and thus racemic) clenbuterol from food contamination (stereoisomerically depleted clenbuterol) was considered. Employing deuterated clenbuterol as internal standard, the target analytes were extracted from human urine by means of concerted liquid‐liquid and solid‐phase extractions and subjected to chiral liquid chromatography hyphenated to high resolution/high accuracy mass spectrometry with electrospray ionization. RESULTS Both enantiomers of clenbuterol were baseline separated and relative abundances of corresponding labeled and unlabeled stereoisomers were determined, demonstrating that the therapeutic use of clenbuterol results in racemic mixtures in urine for at least 24 h while adverse analytical findings presumably originating from food contaminations can yield (−)‐clenbuterol‐depleted pairs of analytes. CONCLUSIONS The determination of relative abundances of clenbuterol enantiomers can indicate the ingestion of clenbuterol via contaminated food; however, depletion of (−)‐clenbuterol in edible animal tissue is time‐dependent and thus results can still be inconclusive as to the inadvertent ingestion of clenbuterol when clenbuterol administration to animals was conducted until slaughter. Copyright © 2013 John Wiley & Sons, Ltd.